(3efXheI aj GdQVGY hTQMgGs - (3GdehShj, GdCUagGfj, GdfLaj, GdYGedj, , UOQ GdOjf, eMeO Hf UGdM Hf eMeO Hf Rjf GdYGHOjf, J(B1264(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj COQ CNdGa aVdg HYehe aUdg(B... (3CeG HYO, agPg efXheI aj GdQVGY(B...s
(3BNQgG (B:s
(3GdGQJVGY ef CYeGe GdcHQi hCNhGdgG hhVhM gPG GdbSe(B...s
(3JHUQI GdeDda (B:s
(3JGQjN haGJg aj eYLe GdeDdajf(B: 1263(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B164s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B355s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B355s
Keywords: (3abg GdePGgH GdCNQis